The expanded Kinesin-13 repertoire of trypanosomes contains only one mitotic Kinesin indicating multiple extra-nuclear roles. - Wickstead, W; Carrington, J; Gluenz, E; Gull, K (Public Library of Science, 2010)
BACKGROUND: Kinesin-13 proteins have a critical role in animal cell mitosis, during which they regulate spindle microtubule dynamics through their depolymerisation activity. Much of what is known about Kinesin-13 function emanates from a relatively small sub-family of proteins containing MCAK and Kif2A/B. However, recent work on kinesins from the much more widely distributed, ancestral Kinesin-13 family, which includes human Kif24, have identified a second function in flagellum length regulation that may exist either alongside or instead of the mitotic role. METHODOLOGY/PRINCIPAL FINDINGS: The African trypanosome Trypanosoma brucei encodes 7 distinct Kinesin-13 proteins, allowing scope for extensive specialisation of roles. Here, we show that of all the trypanosomal Kinesin-13 proteins, only one is nuclear. This protein, TbKIN13-1, is present in the nucleoplasm throughout the cell cycle, but associates with the spindle during mitosis, which in trypanosomes is closed. TbKIN13-1 is necessary for the segregation of both large and mini-chromosomes in this organism and reduction in TbKIN13-1 levels mediated by RNA interference causes deflects in spindle disassembly with spindle-like structures persisting in non-mitotic cells. A second Kinesin-13 is localised to the flagellum tip, but the majority of the Kinesin-13 family members are in neither of these cellular locations. CONCLUSIONS/SIGNIFICANCE: These data show that the expanded Kinesin-13 repertoire of trypanosomes is not associated with diversification of spindle-associated roles. TbKIN13-1 is required for correct spindle function, but the extra-nuclear localisation of the remaining paralogues suggests that the biological roles of the Kinesin-13 family is wider than previously thought.